Early and Late complications associated with Open Modified Janeway Gastrostomy, Under Local Anesthesia in patients with Head & Neck Tumors - Khan, Fatima Zehra; Ali, Mir Arsalan; Shafiq Ur Rehman; Ali Shah, Syed Mustafa; Nisar, Maheen; Abubaker, Zohaib Jawed (International Journal of Endorsing Health Science Research, 2020)
Background: Percutaneous Endoscopic Gastrostomy (PEG) is the primary modality for patients requiring long-term enteric feeding and stomach decompression, it has the potential for complications. Therefore, an open surgical gastrostomy presents as an appropriate alternative for patients not viable for an endoscopic approach. The purpose of the study was to assess the complications associated with Open Modified Janeway Gastrostomy (OMJG) in patients with head & neck tumors and determine their post-operative pain and satisfaction scores. Methodology: A cross-sectional study was conducted at Ziauddin Hospital, North Nazimabad Campus, Karachi, from May 2015 and November 2019. Patients undergoing Open Modified Janeway Gastrostomy were included in this study. Patients with over 18 years of age and who had feeding needs extending beyond 30 days were included in this study. Outcomes measured included length of stay, operating time, complications, surgical satisfaction and post-operative pain. Chi-square test, with a 95% confidence interval, was used to evaluate any association of complications with patient demography and post-treatment parameters. Results: A total of 27 patients participated in this study with the mean age of 56 ± 11.9 years. Complications were not significantly associated with gender, age, mortality or cancer stage. 24 (88.9%) had no post-operative complications, 2 presented with early complications (<14 days post-surgery) and 1 with late complications (>14 days post-surgery). No significant changes were found in activities, sleep or mood. On average, patients reported low pain scores (3.78 ± 1.22), and patient satisfaction was high after opting for OMJG (8.44 ± 0.89). Conclusion: OMJG was found an effective procedure for the insertion of a feeding tube when endoscopic procedures are not feasible, with minimal complications and post-operative pain. It provides more cumulative benefits than other available methods.